2004
DOI: 10.1373/clinchem.2004.031773
|View full text |Cite
|
Sign up to set email alerts
|

Serum Copper Is Decreased in Premature Newborns and Increased in Newborns with Hemolytic Jaundice

Abstract: bined with the individual protein testing capacity of the WB. The assay can be tailored to the requirements of screening or confirmatory testing as well as to the needs of specific vaccine studies. Vaccine trials could benefit greatly from a PBA that differentiates protected from infected individuals. Because large-scale vaccine studies are likely to be conducted in settings where conditions may not permit easy handling of fresh blood specimens, the DBS technology constitutes an attractive alternative for spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Spontaneous preterm birth reduces the pregnancy duration with resultant increased maternal serum concentrations and reduced fetal hepatic stores. Clinical research indicates that serum concentrations of selenium, copper, and zinc are higher in term infants than in preterm infants [20][21][22][23][42][43][44]. Consequently, with adequate nutrition, serum concentrations of selenium, copper, and zinc would be expected to be higher in the serum of women delivering preterm as there is reduced time for the mother to pass these trace elements to the placenta and fetus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous preterm birth reduces the pregnancy duration with resultant increased maternal serum concentrations and reduced fetal hepatic stores. Clinical research indicates that serum concentrations of selenium, copper, and zinc are higher in term infants than in preterm infants [20][21][22][23][42][43][44]. Consequently, with adequate nutrition, serum concentrations of selenium, copper, and zinc would be expected to be higher in the serum of women delivering preterm as there is reduced time for the mother to pass these trace elements to the placenta and fetus.…”
Section: Resultsmentioning
confidence: 99%
“…Copper is an essential cofactor for numerous enzymes involved in various biological processes. The effect of maternal copper concentration is not well understood with some studies suggesting increased preterm birth with copper deficiency [20][21][22][23] and others reporting no association [24,25]. Zinc is a crucial component of many metalloenzymes participating in protein and carbohydrate metabolism, nucleic acid synthesis, and antioxidant functions through the Cu/Zn superoxide dismutase [26].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, zinc and copper levels were found to be reduced by 19% and 42%, respectively, in preterm vs. term placentas [34]. Finally, in a study by Schulpis et al [35] on neonates with jaundice, lower serum copper concentrations were reported for premature neonates compared to full-term neonates in both hemolytic and non-hemolytic jaundice groups. It was proposed that this lower serum copper could be secondary to the liver immaturity in preterm infants which leads to the lack of sufficient accumulation of copper [35].…”
Section: Discussionmentioning
confidence: 85%
“…Finally, in a study by Schulpis et al [35] on neonates with jaundice, lower serum copper concentrations were reported for premature neonates compared to full-term neonates in both hemolytic and non-hemolytic jaundice groups. It was proposed that this lower serum copper could be secondary to the liver immaturity in preterm infants which leads to the lack of sufficient accumulation of copper [35]. Another finding to emerge fi"om this study is the difference in maternal and neonatal Zn and Cu between term neonates with LBW and preterm neonates.…”
Section: Discussionmentioning
confidence: 89%
“…Aliquots of human serum were used as control materials to assess the precision of the Cu determinations. The inter‐assay CV was 4.1% (17).…”
Section: Methodsmentioning
confidence: 99%